Implementation of Education and Training Program Evaluation (Universitas Negeri Semarang, 2022)
This study aims to describe the program evaluation model Context, Input, Process, and Product in the training of office administration managers at BBPLK Semarang. This research is evaluative research using a qualitative descriptive approach. Data collection techniques were carried out using observation, interviews, and documentation methods. Primary data collection uses observation instruments while secondary data is obtained through documentation and interviews. The research subjects comprised the head of the institution, the head of evaluation and reporting, a training instructor and two trainees. Data analysis techniques used are data collection, data reduction, data presentation, and conclusion. The results obtained in this study are seen from the Context Analysis of the needs and educational background of the training carried out by the training organizers by the planning. Judging from the input, the training was organized well and neatly. Instructors, curriculum, educational facilities, and infrastructure that have been well prepared to support the process Judging from the Process The training schedule compiled is carried out according to how, the performance is very good in preparing all training needs, activities run as expected and evaluation of activities carried out by collecting responses from the trainees and reviewed properly so that program improvements continue to be made. Judging from the product, the participants could understand both theoretically and practically. The conclusions of this study indicate that in the context of organizing training for office administration managers, can develop and organize competency-based training programs with national work competency standards.